"Ex‐vivo" T‐cell depletion in allogeneic hematopoietic stem cell transplantation: New clinical approaches for old challenges. (21st May 2021) - Diaz, Miguel A.; Gasior, Mercedes; Molina, Blanca; Pérez‐Martínez, Antonio; González‐Vicent, Marta
Abstract: Allogeneic transplantation still remains as standard of care for patients with high‐risk hematological malignancies at diagnosis or after relapse. However, GvHD remains yet as the most relevant clinical complication in the early post‐transplant period. TCD allogeneic transplant is now considered a valid option to reduce severe GvHD and to provide a platform for cellular therapy to prevent relapse disease or to treat opportunistic infections.